2017
DOI: 10.1007/s41465-017-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Three Stages of Retrieval from Secondary Memory in a Double-Blinded, Placebo-Controlled, Randomized Working Memory Training Study

Abstract: Working memory (WM) is the ability to temporarily store and retrieve a limited amount of information during complex cognitive activities, especially in the face of distraction. The dual-component model describes WM as including active maintenance in primary memory (PM) and cuedependent search and retrieval from secondary memory (SM). Previously, researchers have found that WM training (WMT) fails to enhance SM capacity, a component that mediates the relationship between WM and fluid reasoning (gF). Thus, a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…The main finding of the present study, which is that developing the students' VMs increased their motivation to read, is in line with the study conducted by Ralph et al (2017), which found that the participants' motivation, particularly their intrinsic motivation, increased when their short-term memories were developed via the use of specific techniques.…”
Section: Discussionsupporting
confidence: 91%
“…The main finding of the present study, which is that developing the students' VMs increased their motivation to read, is in line with the study conducted by Ralph et al (2017), which found that the participants' motivation, particularly their intrinsic motivation, increased when their short-term memories were developed via the use of specific techniques.…”
Section: Discussionsupporting
confidence: 91%
“…It is yet unclear when and under which circumstances WM training elicits far transfer effects, as the mechanisms underlying potential transfer effects have been largely neglected in much of past research (cf. von Bastian & Oberauer, 2014; for notable exceptions, see Gibson, Gondoli, Johnson, Steeger, & Morrissey, 2012; Hussey et al, 2016; Lilienthal, Tamez, Shelton, Myerson, & Hale, 2013; Ralph et al, 2017; Waris, Soveri, & Laine, 2015). Moreover, any meta-analytic findings must be interpreted with caution, as they are based on studies that often suffered from methodological issues such as evaluating WM training effects relative to no-contact control groups, using single transfer measures, or low statistical power (cf.…”
mentioning
confidence: 99%
“…Following the method described in the previous section, a total of 16 articles were selected, six of which implemented training in verbal and visuospatial working memory [44,53,[124][125][126][127], one focused on verbal working memory interventions [33], two specifically targeted visuospatial working memory development [34,128], and two stimulated central working memory or did not specify the specific working memory skill they targeted [70,129]. It is noteworthy that two studies conducted combined training of working memory, inhibitory control, and cognitive flexibility [130] or working memory and inhibitory control [19], and only one of the selected studies addressed inhibitory control training individually [34].…”
Section: Resultsmentioning
confidence: 99%